Mecanismos intracelulares envolvidos na resposta anti-proteolítica da estimulação ocitocinérgica em músculos esqueléticos de ratas - Santos, Tatiane de Oliveira (2023)
INTRACELLULAR MECHANISMS INVOLVED IN OXYTOCIN RECEPTOR- INDUCED ANTIPROTEOLYTIC EFFECTS IN RAT SKELETAL MUSCLE. Tatiane de Oliveira Santos, Mestrado em Ciências Fisiológicas, UFS, São Cristóvão/SE, 2023. Although it has been previously demonstrated that the stimulation of oxytocin (OT) receptors can control skeletal muscle mass in vitro and in vivo, the intracellular mechanisms that mediate this effect are still poorly understood. Thus, oxidative skeletal muscles of rats were isolated and incubated with i) OT, ii) a non-peptide selective agonist (WAY-267,464), and iii) an antagonist (atosiban) of OT receptors (OTR), and overall proteolysis was evaluated. The results indicated that both OT and WAY-267,464 (WAY) attenuated muscle proteolysis, and this effect was blocked by the addition of atosiban. Furthermore, it was observed that the WAY-induced anti- catabolic action on protein metabolism is independent of the coupling between OTR and Gαi, as it was insensitive to pertussis toxin (PTX). On the other hand, inhibition of inositol triphosphate receptors (IP3R), which mediates Ca2+ release from the sarcoplasmic reticulum to the cytoplasm, completely blocked the increase in the contents of Ca2+ -dependent protein kinase (PKC) phosphorylated substrates and both Akt and FoxO1 phosphorylation, consequently leading to a decrease in LC3 (an autophagic/lysosomal marker) and total proteolysis induced by WAY. Similar results were obtained in WAY-incubated muscles in the presence of triciribine, an Akt inhibitor. Taken together, these data indicate that OTR produces skeletal muscle protein-sparing effects through a Gαq/IP3R/Ca2+ -dependent pathway and crosstalk with Akt/FoxO1 intracellular signaling, which consequently decreases the expression of genes related to atrophy, such as LC3 and muscle proteolysis.